2019
DOI: 10.1186/s13075-019-1820-3
|View full text |Cite
|
Sign up to set email alerts
|

Reversible SAHH inhibitor protects against glomerulonephritis in lupus-prone mice by downregulating renal α-actinin-4 expression and stabilizing integrin-cytoskeleton linkage

Abstract: BackgroundGlomerulonephritis is one of the major complications and causes of death in systemic lupus erythematosus (SLE) and is characterized by glomerulosclerosis, interstitial fibrosis, and tubular atrophy, along with severe persistent proteinuria. DZ2002 is a reversible S-adenosyl-l-homocysteine hydrolase (SAHH) inhibitor with potent therapeutic activity against lupus nephritis in mice. However, the molecular events underlying the renal protective effects of DZ2002 remained unclear. This study is designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Although the role of ACTN4 in liver brosis is underreported at present, it's been associated with kidney brosis and glomerulosclerosis progression. Notably, decreased expression of ACTN4 could delay kidney brosis development [24][25][26] . Furthermore, ACTN4 interaction with TRIP13 in HCC activates the AKT/mTOR pathway, triggering EMT 23 , a process signi cant to the progression of liver brosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of ACTN4 in liver brosis is underreported at present, it's been associated with kidney brosis and glomerulosclerosis progression. Notably, decreased expression of ACTN4 could delay kidney brosis development [24][25][26] . Furthermore, ACTN4 interaction with TRIP13 in HCC activates the AKT/mTOR pathway, triggering EMT 23 , a process signi cant to the progression of liver brosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the concentrations can increase during the progression of several inflammatory and autoimmune diseases, such as chronic kidney disease, glomerulonephritis, and after renal transplantation [27,69]. It has been observed that, differently from other tissue, such as the brain, where NGF promoted cell growth, differentiation, and survival, high levels of NGF in the renal tubular cells promote growth arrest and apoptosis [70][71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…Surface marker and intracellular transcription factor staining were conducted and analyzed using our previously reported methods [29]. Briefly, for surface marker and intracellular transcription factors, cells were collected and stained with FITC-, PE-, PerCP-Cy5.5-, APC-, BV421-, or BUV395-conjugated monoclonal antibodies (mAbs) for membrane molecules or intracellular staining after being blocked with anti-mouse CD16/CD32 (Fc Receptor Block, eBioscience, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Because of the relatively long turnover rate of SAHH, the irreversible inhibitors manifest significant toxicity, whereas toxicity of type III inhibitors show greatly lowered yet still retain a parallel ability to block the enzyme’s activity [25]. The reversible type III SAHH inhibitor DZ2002 [methyl-(adenin-9-yl)-2-hydroxybutanoate] has been found to have an immunomodulatory function and to alleviate disease in several inflammatory and autoimmune animal models [2529]. It is reported that DZ2002 prevented lupus-like disease from developing in both BXSB and MRL-Faslpr mouse models and DZ2002 ameliorated imiquimod-induced psoriasis-like skin lesions in mice via suppression of T cell-derived IL-17 [24, 30].…”
Section: Introductionmentioning
confidence: 99%